2022
DOI: 10.1093/annweh/wxac068
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Stone Fabrication Work Releases Volatile Organic Compounds Classified as Lung Irritants

Abstract: Engineered stones are often characterized for their crystalline silica content. Their organic composition, particularly that of the emissions generated during fabrication work using hand-held power tools, is relatively unexplored. We forensically screened the emissions from dry-cutting 12 engineered stone products in a test chamber for their organic composition by pyrolysis-gas chromatography-mass spectrometry (GC-MS) plus selected traditional capture and analysis techniques. Phthalic anhydride, which has a Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…15,21 Recent work by us, and others, has shown that a wide range of VOCs are emitted when cutting stone materials, in varying concentrations depending on the ES samples. 18,26 Epidemiological studies indicate that inhalation of airborne VOCs is associated with reduced lung function, exacerbation of asthma and increased rates of obstructive lung diseases and lung cancer. 47 Animal studies have shown that exposure to low-dose VOCs (formaldehyde, benzene, toluene and xylene) produces bronchial and lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,21 Recent work by us, and others, has shown that a wide range of VOCs are emitted when cutting stone materials, in varying concentrations depending on the ES samples. 18,26 Epidemiological studies indicate that inhalation of airborne VOCs is associated with reduced lung function, exacerbation of asthma and increased rates of obstructive lung diseases and lung cancer. 47 Animal studies have shown that exposure to low-dose VOCs (formaldehyde, benzene, toluene and xylene) produces bronchial and lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…47 Animal studies have shown that exposure to low-dose VOCs (formaldehyde, benzene, toluene and xylene) produces bronchial and lung inflammation. 48 Low molecular weight VOCs, such as phenanthrene and fluorene which we have identified during ES processing, 18 induce oxidative stress and inflammation in human lung epithelial cells (A549) and the combined action of both are more potent than their individual effects. 24 Therefore, urgent research is needed to assess the contribution of VOCs generated from processing ES to the development of severe and progressive silicosis in this occupational group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a growing concern regarding the potential impact of inhaling the organic compounds liberated by processing ES, potentially from the binding resin which represents up to 14%, by weight, of ES [23,24]. Recently, we showed that ES processing generates volatile organic compounds (VOCs) such as styrene and phthalic anhydride, both of which have been linked to lung disease [21,25,26]. Other low-molecular weight VOCs identi ed during ES processing have also been observed to induce oxidative stress and in ammation in human lung epithelial cells [27].…”
Section: Introductionmentioning
confidence: 99%